If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(m-8)=-2
We move all terms to the left:
2(m-8)-(-2)=0
We add all the numbers together, and all the variables
2(m-8)+2=0
We multiply parentheses
2m-16+2=0
We add all the numbers together, and all the variables
2m-14=0
We move all terms containing m to the left, all other terms to the right
2m=14
m=14/2
m=7
| 9y-48=y-16 | | 13+13x=20x-22 | | 18a-6=1 | | -6-n=-17 | | -38+2y-8=3(y-11) | | 4(6n+6)=-168 | | -1+2y-8=3(y-11) | | -1x+9=2x+145 | | (7−b)+(3b+2)=0 | | 1+2y-8=3(y-11) | | 1+3(5w-5)=16 | | -5x-18=-11x+30 | | -5(5+3n)+7=-6(3+8n) | | -(-16-8x)=(6x-4) | | 40+0.30x=20+0.40x | | -12x+3=2x+31 | | 14x+8=41 | | 15p-9=7p+1 | | -(-16-8x)=(6x-4 | | b/11-7b=24/11 | | 4x+2(4x-8)-4=-56 | | X+1/8x=126 | | y/10-70=-67 | | 2×5x=4x | | 10.9+3x-5=13 | | -214=5(7x+2)-3x | | (d)=25+20d | | 2x-3x+4=1 | | (4y+32)-7=15 | | -u+18=201 | | 10=v-1 | | -13.13-13.2z=-3.1z |